Waterborne Paints Based on Polymeric Semiconductor for Attachable Thermoelectric Generators. Issue 2 (28th November 2022) - Zhang, Xiao; Ding, Jiamin; Wang, Dongyang; Dai, Xiaojuan; Ma, Yingqiao; Zhao, Yue; Guan, Bo; Liu, Liyao; Zou, Ye; Zhang, Fengjiao; Di, Chong-an
Abstract : Organic thermoelectric (OTE) materials offer a direct way to harvest electricity from heat resources. Although OTE paints can be coated on irregular heat sources via various solution‐processing techniques, most candidates are only soluble in toxic organic solvents and require complex preparation method, limiting their wide industrial applications. Herein, an environment‐friendly waterborne colloid based on a selenium‐substituted diketopyrrolopyrrole derivative (PDPPSe‐12) is utilized using a miniemulsion process to enable water‐dispersive OTE paints. The doped films not only exhibit prominent electrical conductivity and high Seebeck coefficient, but also show unexpected low thermal conductivity, yielding a maximum power factor and figure of merit value of up to 74.77 ± 1.76 μW m −1  K −2 and 0.14, respectively. More importantly, their application potential in a realistic thermoelectric generator (TEG) on a paper substrate by painting is demonstrated, which possesses an output power of 14.70 nW under a temperature difference of 19 K. For the first time, these results reveal that the fabrication of waterborne OTE paints can decrease the thermal conductivity and its integrated organic TEGs exhibit preferable performance. These results offer valuable insights for designing high‐performance OTE paints toward multiple‐energy supplier systems in an environmentally friendly way. Abstract : Organic thermoelectric paints are prepared from environment‐friendly waterborne colloids of selenium‐substituted diketopyrrolopyrrole derivative by miniemulsion process. FeCl3 ‐doped films exhibit a maximum power factor and figure‐of‐merit value of 74.77 ± 1.76 μW m −1  K −2 and 0.14, respectively. Thermoelectric generators on paper substrates possess an output power of 14.70 nW under a temperature difference of 19 K.